Open science with closed research assessment systems? - Beigel, Maria Fernanda (2021)
An increasingly digital world gives us an unprecedented opportunity to harness the scientific potential inherent to all countries and academic communities. The internet made it possible for scientists on opposite sides of the Earth to collaborate without meeting face to face. The trend towards international co-authorship is picking up speed, in hegemonic and non-hegemonic countries. Scientists can now share their research data by making them freely available online, under terms that enable this research to be re-used, reproduced, redistributed and credited. The open access movement has gradually evolved into an open science movement that seeks to make the entire scientific process more accessible and transparent by sharing data, protocols, software and infrastructure (Persic, Beigel, Hodson & OtiBoateng, 2021). However, daily life at universities and research centres presents performance pressures that counteract these opportunities and slow down the drive for openness, traditionally in the nature of scientific culture.